Changing Trajectory: An Integrated Theoretical View of the Roman Catholic Priest Sex Abuse Scandal. Issue 9 (1st September 2016) - Alexander, Ryan; Birzer, Michael L.
ABSTRACT: The sexual abuse of children by Roman Catholic priests across the United States is a direct result of access to children, and that access changes across the life-course of individual priests. Turning points affect not only an individual priest's motivation to commit the crime, but also the suitability of a target. Guardianship of the victim and the surveillance of the offender play a salient role in facilitating the opportunity for the sexual assault of a child. Two criminological theories are germane to how contextual elements of the abusive situation can fluctuate across the life course: (1) Life Course Theory and (2) Routine Activity Theory.